1998
DOI: 10.1159/000008610
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Albendazole Sulfoxide Solution on the Scolices and the Hepatobiliary System

Abstract: The use of scolocidal solutions in the hepatobiliary system may result in caustic sclerosing cholangitis. In this study, the effectivenes of a biological metabolite of albendazole, albendazole sulfoxide, on scolices and the hepatobiliary system was evaluated. In the in vitro study, it was found that 100 µg/ml albendazole sulfoxide solution had strong scolocidal effect in 15 min. In the in vivo study, two experimental groups, each consisting of 8 rabbits aged 3–4 months and weighing 2,500 ± 250 g, 100 µg/ml alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Various scolicidal agents such as 95% alcohol, 10% povidone iodine, hypertonic saline, hydrogen peroxide, 5% formalin, silver nitrate, cetrimide, and albendazole have been evaluated for scolicidal effects and hepatobiliary complications in the presence of cystobiliary communications (Landa García et al 1997;Topcu et al 2006;Sahin et al 2004 ). Even though 95% Ethyl alcohol had been found to be 100% effective at the end of 15 min (Erzurumlu et al 1998), severe hepatobiliary complications have been reported for alcohol (Yetim et al 2005). Hypertonic salt water (20%) was found to be 99.5% effective at the end of 10 min (Adas et al 2009), but severe hepatobiliary complications have been reported for 10%-20% NaCl ( Topcu et al pH Time ( Meymerian et al (1963), fatal air embolism and anaphylactic shock have been reported with this scolicidal agent by Adas et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various scolicidal agents such as 95% alcohol, 10% povidone iodine, hypertonic saline, hydrogen peroxide, 5% formalin, silver nitrate, cetrimide, and albendazole have been evaluated for scolicidal effects and hepatobiliary complications in the presence of cystobiliary communications (Landa García et al 1997;Topcu et al 2006;Sahin et al 2004 ). Even though 95% Ethyl alcohol had been found to be 100% effective at the end of 15 min (Erzurumlu et al 1998), severe hepatobiliary complications have been reported for alcohol (Yetim et al 2005). Hypertonic salt water (20%) was found to be 99.5% effective at the end of 10 min (Adas et al 2009), but severe hepatobiliary complications have been reported for 10%-20% NaCl ( Topcu et al pH Time ( Meymerian et al (1963), fatal air embolism and anaphylactic shock have been reported with this scolicidal agent by Adas et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…ABZ sulfoxide is more effective than ABZ sulfone (Adas et al 2009). Twenty microgram per milliliter ABZ sulfoxide killed 5% of the scolices in 15 min, scolicidal activity was 50% with a 50 μg/ mL solution, and it was 100% for a 100 μg/mL solution (Erzurumlu et al 1998). It is known that scolicidal solution injection in the cysts or the biliary system leads to a rise in liver enzyme level.…”
Section: Discussionmentioning
confidence: 99%
“…Although the efficacy of systemic administration is limited and prolonged exposure of albendazole to the biliary tree promotes caustic sclerosing cholangitis, the effects of the albendazole on the biliary system are do not exceed those of 0.9% NaCl. Nevertheless, Erzurumlu et al [9] showed that albendazole has less toxicity on bile duct than other treatments. Direct cystic injection of these drugs offers the advantage of a high intracystic drug concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in farm animals, cystic hydatidosis causes severe economic losses. Although benzimidazole derivatives such as albendazole are used in treatments, there is often an absence of complete recovery after treatment (25). Surgery remains the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%